Rapport management in air traffic control in Malaysian aviation discourse. - Paramasivam, Shamala (John Benjamins Publishing, 2011)
Oral communication is documented as the weakest link in air traffic control interactions and one of the primary causes of aviation accidents and incidents. The language of air traffic control communication is characterised by the use of prescribed phraseologies, and when these are missing, plain language becomes a dominant feature. During plain language use mitigation is recorded as a feature of communication and described as an attribute of communication in crews classified as high in safety performance. The present study departs from this observation and seeks to examine the linguistic features for rapport management in air traffic control in non-routine situations in the Malaysian context. Managing the pilot-controller relationship is categorised as one of the dominant communicative functions in air traffic control and a category that is associated with the use of politeness markers. An examination of the language functions in this category and their associated forms vis-à-vis features of politeness are considered useful for training in air traffic communication. Pragmatics is used in this study as the approach to discourse analysis and Spencer-Oatey's (2000b) understanding of politeness as 'rapport management' is employed as the framework for data analysis. The study draws on both audio-recordings of radiotelephony communication in role-play situations involving expert Malaysian controllers taking on roles as pilot and controller, as well as transcripts of real-life radiotelephony communication between Malaysian controllers and international pilots. The findings show that the interactions are primarily oriented to rapport-maintenance. The linguistic devices for rapport management include justifications, terms of address, conventionally polite expressions such as 'please', modals, and conditional language use. Rapport management is shown to help foster shared mindfulness and team thinking between controllers and pilots.